(untitled) (Research, Society and Development, 2022)
Cities radiate an environment of infrastructure necessary for quality of life. A network of transport, housing and sanitation flows marks the city as a place that requires constant planning and surveillance. The disorderly growth of cities is related to the insufficient planning of urban policies and the preponderance of individual, financial and political interests. The purpose of this article is to analyze recent academic publications on urban management and planning necessary to reflect on the potential socio-environmental and legal effects of urban sprawl, which has not always been adequate for quality of life. The starting point is the analysis of the legal and illegal city and their dichotomies. For this purpose, a descriptive research was carried out, focusing on the last fifty years. As methodological support, there is a review of the literature published in the last six years, compared under the hypothetical-deductive method. The results indicated a historical absence of planning or strategy in urbanization policies, which produces dysfunctions or irregularities in cities, in land occupation. Mere formal regularization is not necessarily the solution to the problem, as it can generate peripheralization or displacement of this irregularity, encourage real estate speculation, financialization of space to the detriment of socio-environmental aspects and urban infrastructure.